Muslim сommunities in the USA and Western Europe: patterns of electoral behavior - Inna V. Shumilina (Научно-аналитический вестник Института Европы РАН)
The year 2024 will see electoral events of particular importance: not only will they, like those that preceded them, determine the direction of development of socio-political life in the United States and Western Europe for at least the next four years, but they will also most likely influence the political situation in the world as a whole, especially in Europe (the conflict around Ukraine) and the Middle East (the Palestinian-Israeli confrontation, tensions around Iran). Due to demographic and other factors, Muslim communities on both sides of the Atlantic play an increasingly important role in these electoral processes. The article examines the models of their electoral behavior under the influence of various concepts and mechanisms of their adaptation in the respective societies – the «melting pot» in the United States and «multiculturalism» in Western Europe. Today, Kamala Harris appears to be a consensus figure for most American Muslims, which increases her chances in the November 2024 elections.